Monitoring dan Evaluasi Light Rail Transit (LRT) Sumatera Selatan - Yunianti, Wina; Buchari, Erika; Agustien, Melawaty (Universitas Jember, 2023)
Palembang is the first city in Indonesia to have light rail transit. Enthusiasm for the LRT was high enough that the number of passengers reached 2,619,159 people in 2019. 2020 there was a drastic decline due to the COVID-19 pandemic, and the number of passengers decreased to 1,053,637. The problem in the field is that after COVID-19, there was a decrease in the number of passengers by up to 59.8% from 2019. Apart from that, there is no monitoring system to monitor the growth of LRT passengers. Therefore, Monitoring and evaluation need to be carried out to monitor and supervise the progress of policy performance implemented by the South Sumatra Light Rail Center and assess whether the performance is on target and by its objectives. This research aims to evaluate the performance of the LRT and the policies that have been implemented. This research uses operational data, analytical methods, and descriptive analysis. Research results show that the number of passengers in 2023 will increase by 10,299 per day compared to 2022, of 8,436 per day. Several policies implemented by the light rail center to increase LRT passengers include providing shopping trolleys at Ampera station, student subscription cards, and others. People with disabilities and the community, as well as delivering feeder transportation. ABSTRAK Kota Palembang merupakan kota pertama di Indonesia yang memiliki kereta api ringan listrik. LRT Sumatera Selatan. Antusiasme masyarakat terhadap LRT cukup tinggi sehingga jumlah penumpang mencapai 2.619.159 pada tahun 2019. Tahun 2020 terjadi penurunan yang drastis akibat pandemic covid-19, jumlah penumpang menurun menjadi 1.053.637 penumpang. Masalah yang terlihat dilapangan saat habis Covid 19 adalah penurunan jumlah penumpang sampai 59,8% dari tahun 2019. Selain itu belum ada system monitoring untuk mengawal pertumbuhan penumpang LRT. Monitoring dan evaluasi dilakukan untuk memantau dan mengawal progres kinerja dari kebijakan yang dilakukan oleh balai kereta api ringan sumatera Selatan dan menilai kinerja apakah tepat sasaran dan sesuai tujuannya karena jika tidak di monitor bisa terjadi penyimpangan. Tujuan penelitian adalah mengevaluasi kinerja LRT dan kebijakan yang telah dilakukan. Penelitian menggunaka metode analisis data operasional dan analisis deskriptif. Hasil penelitian menunjukan penumpang tahun 2023 meningkat 10.299 perhari yang sebelumnya 8.436 perhari pada tahun 2022. Balai kereta api ringan melakukan beberapa kebijakan untuk meningkatkan penumpang LRT seperti Tas Troley belanja di stasiun ampera, kartu berlangganan untuk pelajar, disabilitas, dan masyarakat serta menyediakan angkutan feeder.